Five-year follow-up outcomes after Descemet's stripping automated endothelial keratoplasty: a retrospective study. Issue 1 (29th January 2020) - Wakimasu, Koichi; Kitazawa, Koji; Kayukawa, Kanae; Yokota, Isao; Inatomi, Tsutomu; Hieda, Osamu; Sotozono, Chie; Kinoshita, Shigeru
Abstract : Objective: To assess graft survival and endothelial cell density (ECD) over a 5-year follow-up period after Descemet's stripping automated endothelial keratoplasty (DSAEK). Methods and analysis: This retrospective study involved 130 eyes of 130 consecutive patients with Fuchs endothelial corneal dystrophy (FECD), non-FECD bullous keratopathy (BK) (non-FECD) or BK post-trabeculectomy or tube-shunt surgery (glaucoma with bleb) who underwent DSAEK between August 2007 and January 2012 and were followed for more than 5 years postoperatively. Patients with previous keratoplasty, graft suture failure, primary graft failure, postoperative endophthalmitis and ocular infection were excluded. Graft survival and ECD was then examined in all patients who underwent DSAEK and completed the postoperative follow-up period. The association between clinical factors and 5-year graft survival after DSAEK was analysed with multivariate logistic regression analysis. Results: The overall graft survival rate at 5 years postoperatively was 85%, yet significantly poorer in the glaucoma with bleb eyes (47%) than in the FECD (100%) or non-FECD (90%) eyes (p<0.01, log-rank test). In the FECD, non-FECD and glaucoma with bleb eyes, the mean ECD at 5 years postoperatively was 1054 cells/mm 2, 1137 cells/mm 2 and 756 cells/mm 2, respectively. Multivariate logistic regression analysis showed history of trabeculectomy or tube-shunt surgery and postoperative allograft rejection to be negative factors for graft survival at 5 years after DSAEK (OR 0.01, 95% CI 0.00 to 0.10 and OR 0.02, 95% CI 0.00 to 0.33, respectively). Conclusion: Our findings show that at 5 years postoperatively, the surgical outcome after DSAEK was poorer in eyes after trabeculectomy or tube-shunt surgery. Trial registration number: UMIN000024891.